The Indirect Tax Credit in Domestic Legislation and in the Agreements to Avoid Double Taxation Subscribed by Peru - Flores Benavides, Rodrigo (2014)
In the first section of the article, the two types of international double taxation, as well as the main mechanisms for its elimination, are reviewed. Subsequently, is analyzed the indirect tax credit in Peruvian tax law. The main section is devoted to the indirect tax credit set forth in the tax treaties concluded by Peru, including its practical application and the relation between such treaties and domestic legislation.